2021
DOI: 10.1111/jcmm.16229
|View full text |Cite
|
Sign up to set email alerts
|

Val‐Val‐Tyr‐Pro protects against non‐alcoholic steatohepatitis in mice by modulating the gut microbiota and gut‐liver axis activation

Abstract: Val‐Val‐Tyr‐Pro (VVYP) peptide is one of the main active components of Globin digest (GD). Our previous studies indicated that VVYP could protect against acetaminophen and carbon tetrachloride‐induced acute liver failure in mice and decrease blood lipid level. However, the effects and underlying mechanisms of VVYP in the treatment of non‐alcoholic steatohepatitis (NASH) have not been discovered. Our present study was designed to investigate the preventive effect of VVYP on NASH and its underlying specific mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 95 publications
1
13
0
Order By: Relevance
“…Gut microbiota, as an important component of the intestine, plays an active role in UA excretion [ 9 , 47 ]. In accordance, previous studies indicated that the anti-hyperuricemic effects of some oligopeptides were mediated by the gut microbiota, such as tuna meat oligopeptides [ 40 ], Val-Val-Tyr-Pro peptide [ 48 ], and Apostichopus japonicus oligopeptide [ 49 ]. As reported, the diversity of intestinal flora in the hyperuricemia group is generally lower than that in the normal group [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…Gut microbiota, as an important component of the intestine, plays an active role in UA excretion [ 9 , 47 ]. In accordance, previous studies indicated that the anti-hyperuricemic effects of some oligopeptides were mediated by the gut microbiota, such as tuna meat oligopeptides [ 40 ], Val-Val-Tyr-Pro peptide [ 48 ], and Apostichopus japonicus oligopeptide [ 49 ]. As reported, the diversity of intestinal flora in the hyperuricemia group is generally lower than that in the normal group [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…45 Similar finding was also demonstrated in the mitigating effect of Val-Val-Tyr-Pro (VVYP) peptide against non-alcoholic steatohepatitis, in which the abundance of Desulfovibrionaceae was also increased. 46 These findings indicated that modulation of the gut microbiota may partly explain the beneficial effects of mAPS against NAFLD.…”
Section: Discussionmentioning
confidence: 93%
“…However, the precise association between gut microbiota and NASH presently remains unclear (45). Except for the perturbation of the intestinal microbiota occurring in patients with NASH (46), the 16S rRNA sequence data showed microbiota dysbiosis in NAFLD and NASH mouse models (47)(48)(49). The current study showed that YZH modulated the composition of gut microbiota rather than increasing the variety of intestinal microbiota.…”
Section: Discussionmentioning
confidence: 56%